Comparison of Central Composite and Box-Behnken design in optimization of turbidity removal using nanocellulose filter paper (Neolarmarckia cadamba) - jeffi, nurazlin (Progress in Engineering Application and Technology, 2021)
Filtration process using Neolamarckia cadamba filter paper for dye effluents removal from dye industrial wastewater offer a favorable solution which suits well with the definition of sustainability. This study was aimed at using the Central Composite Design (CCD) and Box-Behnken Design (BBD) to compare the efficiency and to elucidate the main interacting parameters of turbidity removal using MINITAB 18 Statistical Software. At optimized conditions, the filtration process would be able to achieve 99.39% turbidity removal efficiency for CCD and 99.69% for BBD, respectively. The optimum conditions for the filtration process of CCD model on turbidity removal are initial turbidity of 66NTU, pH of 6.4 and initial temperature of 36ºC while BBD is 75NTU for initial turbidity, pH of 5.5 and initial temperature of 30ºC. Both design of experiments were successfully applied in this study. R2 values of 73.42% and 90.95% for CCD and BBD models, which indicate that both models are statistically significant with each other. However, BBD consumes limited time with fewer experimental runs, is efficient, and is commonly used in wastewater treatment. Therefore, this study showed that BBD model was the best option in terms of number of required experiments and quality of the obtained data.